Israeli-Egyptian Gas Cooperation: Significance of Political Domestic Factors [version 2; peer review: 2 approved, 1 approved with reservations] - Artur Skorek; Michał Lipa (Stosunki Międzynarodowe)
Israeli gas discoveries and the Egyptian energy crisis prompted gas trade talks between the two countries. A letter of intention signed in 2014 gave the impression that Israel would soon supply its neighbor with much-needed energy resources. This development seemed to be an obvious result of the economic and political needs of both states and the recent transformation of the regional international system. Surprisingly, the negotiations became prolonged and were marred by tensions and backtracking. The article aims to present the domestic factors in Egypt and Israel that shape the approach of these countries to mutual energy cooperation and to assess their current and future impact on the energy outlook of the Eastern Mediterranean.